Successful treatment of triple EGFR mutation T785A/L861Q/H297_E298 with afatinib. Issue 13 (19th May 2021) - Longo, Vito; Catino, Annamaria; Montrone, Michele; Pizzutilo, Pamela; Pesola, Francesco; Marech, Ilaria; Capone, Iolanda; Prelaj, Arsela; Galetta, Domenico
Abstract: Patients with non‐small cell lung cancer (NSCLC) and uncommon epidermal growth factor receptor ( EGFR ) mutation are characterized by high heterogeneity, and globally considered to have a worse prognosis than patients with the two common mutations; exon 19 deletion, and exon 21 L858R. Nevertheless, some uncommon mutations do confer sensitivity to tyrosine kinase inhibitors (TKIs) which is comparable with common mutations. In particular, some compound EGFR mutations seem to be characterized by a favorable prognosis. Unfortunately, the rarity of complex EGFR mutations results in difficult clinical decision‐making. Herein, to the best of our knowledge, we report the first case of an NSCLC patient with an EGFR triple mutation containing T785A/L861Q/H297_E298 who was successfully treated with afatinib. Abstract : Patients with NSCLC and uncommon EGFR mutation are globally considered to have a poor prognosis. Nevertheless, some uncommon mutations confer sensitivity to tyrosine kinase inhibitors. In particular, some compound EGFR mutations appear to be characterized by a favourable prognosis. Herein, we report the first case of an NSCLC patient with an EGFR triple mutation containing T785A/L861Q/H297_E298 successfully treated with afatinib.